Dialektika Moral Etik Penafsir Otoritarianisme: Pendekatan Hermeneutika Negosiatif Khaleed Moh. Abou El-Fadl - Nur Kholik; Subiantoro Subiantoro; Muhammad Wafa' (Jurnal Keislaman, 2023)
Man is a religious being created by God so that it becomes commonplace when God sends agama for man. But it is not an easy matter to understand God's will through His symbols. While the Prophets and Apostles were alive, humans could directly confirm the appearance of the symbol. But when the Nth breed of abian is cut off from the present era, then it raises the potential for "polemics". Most evident is the struggle for claims as the most authoritative representative of the true God. As a result, predictably, they fighters recite fatwas, claim the truth to the point of negate different interpretations. This is what Abou Fadl is concerned about, where individuals or institutions (special representatives) have actually deprived God of authority and exceeded the authority of the real mandate. At the same time, this attitude of authoritarianism causes the stagnation of epistemology in the process of exploration of the determination of the meaning of the text. On the same occasion Abou Fadl offers a Hermeneutic approach oriented towards an authority of text interpretation by negotiating the text, author, and reader.